Bordetella pertussis and Bordetella bronchiseptica filamentous hemagglutinins are processed at different sites. Issue 8 (20th June 2018) - Jurnecka, David; Man, Petr; Sebo, Peter; Bumba, Ladislav
Abstract : Filamentous hemagglutinin (FHA) mediates adherence and plays an important role in lower respiratory tract infections by pathogenic Bordetellae . The mature FHA proteins of B. pertussis (Bp‐FHA) and the B. bronchiseptica (Bb‐FHA) are generated by processing of the respective FhaB precursors by the autotransporter subtilisin‐type protease SphB1. We have used bottom‐up proteomics with differential 16 O/ 18 O labeling and show that despite high‐sequence conservation of the corresponding FhaB segments, the mature Bp‐FHA (~ 230 kDa) and Bb‐FHA (~ 243 kDa) proteins are processed at different sites of FhaB, after the Ala‐2348 and Lys‐2479 residues, respectively. Moreover, protease surface accessibility probing by on‐column (on‐line) digestion of the Bp‐FHA and Bb‐FHA proteins yielded different peptide patterns, revealing structural differences in the N‐terminal and C‐terminal domains of the Bp‐FHA and Bb‐FHA proteins. These data indicate specific structural variations between the highly homologous FHA proteins. Abstract : Filamentous hemagglutinins (FHA) of Bordetellae are produced by processing of the ~ 130‐kDa C‐terminal prodomains of their FhaB precursors by the subtilisin‐like protease SphB1. Despite near‐complete sequence conservation of the processed FhaB segments, the SphB1 cleavage sites of FhaB from B. pertussis and B. bronchiseptica differ, yielding diverse C‐terminal sequences of the mature FHA and FHA1 proteins.